Facilitating Proper English Pronunciation in Storytelling by Virtue of Hijaiyah Sound Mediation - Gusdian, Rosalin Ismayoeng; Setyaningrum, Rina Wahyu; Lestiono, Riski (Universitas Brawijaya, 2020)
Story telling has been an icon of local culture preservation. Since local wisdoms knotted in local cultures are prone to be eroded along the changing eras, an effort to bring back and preserve them should be the penultimate concern, before implementing those values in real basis. Folklores have been the media to incarnate those local wisdoms, and thus this book is worth referring to when it comes to the topic of folklores for storytelling. All folklores covered in this book are originating from Indonesia, as the name suggests, â€œNusantaraâ€, served in bilingual versions â€“ Bahasa and English. A series of training and drilling were planned to be conducted in SMP Negeri 02 and 03 Batu so as to project the English pronunciation precision. The stages include the followings: (1) FGD (Focused-Group Discussion) between researchers and the teachers as well as the students to tap challenging sounds susceptible to be mispronounced during storytelling the folklores taken from the book; (2) mapping corresponding English-Hijaiyah sounds to train; (3) modeling by CS Team and English teachers; (4) the studentsâ€™ English pronunciation training by means of Hijaiyah corresponding sounds; (5) reflection and feedback for the betterment of training activities; (6) the studentsâ€™ simulation for storytelling; and (7) video taking and making.